Development of microbial community during primary succession in areas degraded by mining activities - Harantová, Lenka; Mudrák, Ondřej; Kohout, Petr; Elhottová, Dana; Frouz, Jan; Baldrian, Petr (Land degradation & development, 2017)
Together with plants, soil microbial communities play an essential role in the development of stable ecosystems on degraded lands, such as postmining spoil heaps. Our study addressed concurrent development of the vegetation and soil fungal and bacterial communities in the course of primary succession in a brown coal mine spoil deposit area in the Czech Republic across a chronosequence spanning 54 years. During succession, the plant communities changed from sparse plants over grassland and shrubland into a forest, becoming substantially more diverse with time. Microbial biomass increased until the 21st year of ecosystem development and later decreased. Although there was a close association between fungi and vegetation, with fungi mirroring the differences in plant community assemblages, the development of the bacterial community was different. The early succession community in the barren nonvegetated soil largely differed from that in the older sites, especially in its high abundance of autotrophic and free‐living N2‐fixing bacteria. Later in succession, bacterial community changes were minor and reflected the chemical parameters of the soil, including pH, which also showed a minor change with time. Our results show that complex forest ecosystems developed over 54 years on the originally barren soil of the temperate zone and indicate an important role of bacteria in the initial stage of soil development. Although the arrival of vegetation affects substantially fungal as well as bacterial communities, it is mainly fungi that respond to the ongoing development of vegetation.